Leaving Necessity Entrepreneurship Behind: How Entrepreneurs Actualize Desirable Futures - Coffman, Chad D.; Cottle, Griffin W.; Sunny, Sanwar A. (Academy of Management Review, 2025)
Although prior research has documented that some necessity-motivated ventures grow, and later develop into what researchers have traditionally called “opportunity-driven” ventures, the existing dichotomous framework offers no theoretical explanation for how this transition occurs. We build on the actualization view of entrepreneurship to describe the process by which an entrepreneur’s underlying needs—basic, psychological, and self-fulfillment needs—motivate both the desired future states that they envision, and their evaluation of the actions and conditions necessary to actualize the futures they imagine. We then extend actualization theory beyond the identification and evaluation of opportunities to include venture creation. We describe how needs effect the identification of key milestones, the pace at which milestones must be reached, and the level of uncertainty that entrepreneurs are willing to bear. In doing so, we illustrate how basic needs motivation leads to the selection of imitative or replicative actions, but that subsequent needs actualization can free necessity entrepreneurs to pursue voluntary forms of entrepreneurship once their basic needs have been met. Our model invites scholars to go beyond describing the antecedents and outcomes of necessity entrepreneurship, to research aimed at understanding the process through which necessity entrepreneurs transition to more voluntary forms of venturing.